RENEWAL IN ISLAMIC THOUGHT: A COMPARATIVE STUDY OF AHMAD AL-TAYYEB AND HAEDAR NASHIR - Alamuddien Asyrozi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT This article discusses the concept of contemporary Islamic reform through a comparative study of Ahmad al-Tayyeb and Haedar Nashir. Debates on Islamic reform in the modern era have often been examined separately within Middle Eastern or Indonesian contexts, while comparative studies exploring reform models based on global religious authority and modern Indonesian Islamic movements remain limited. This gap is important to address in order to understand the diversity of Islamic reform orientations in responding to the challenges of modernity. This study aims to analyze how both figures define Islamic reform, connect the values of Islamic authenticity with contemporary dynamics, and identify the similarities and differences in their intellectual orientations. The research employs a qualitative library-based approach using descriptive, analytical, and comparative methods. The data were collected from the writings, speeches, and intellectual documents of both figures, supported by literature on tajdid, wasatiyyah, Islamic reform, and Progressive Islam. The findings reveal that both figures reject extremism and the secularization of modernity; however, they differ in their emphasis on Islamic reform. Ahmad al-Tayyeb highlights turath, Islamic moderation, the continuity of scholarly traditions, and interfaith dialogue, whereas Haedar Nashir emphasizes Progressive Islam, social transformation, education, and civic pluralism. The study confirms that Islamic reform evolves contextually, ethically, and institutionally in accordance with the social environments surrounding each intellectual tradition. This research offers a novel contribution by proposing a comparative framework between Islamic reform paradigms rooted in Middle Eastern religious authority and those emerging from modern Indonesian Islamic movements, thereby broadening the understanding of the plurality of contemporary tajdid models. ABSTRAK Artikel ini membahas konsep pembaruan Islam kontemporer melalui kajian komparatif antara Ahmad al-Tayyeb dan Haedar Nashir. Perdebatan mengenai pembaruan Islam pada era modern cenderung dikaji secara parsial dalam konteks Timur Tengah atau Indonesia, sementara studi yang membandingkan model tajdid berbasis otoritas keagamaan global dan gerakan Islam modern Indonesia masih terbatas. Kesenjangan tersebut penting dikaji untuk memahami keberagaman orientasi pembaruan Islam dalam merespons tantangan modernitas. Penelitian ini bertujuan menganalisis cara kedua tokoh mendefinisikan pembaruan Islam, menghubungkan nilai-nilai otentisitas Islam dengan dinamika modern, serta mengidentifikasi persamaan dan perbedaan orientasi pemikiran keduanya. Penelitian menggunakan pendekatan kualitatif berbasis studi pustaka dengan metode deskriptif, analitis, dan komparatif. Data penelitian diperoleh dari karya, pidato, dan dokumen pemikiran kedua tokoh yang dianalisis bersama literatur terkait tajdid, wasatiyyah, reformasi Islam, dan Islam Berkemajuan. Hasil penelitian menunjukkan bahwa kedua tokoh sama-sama menolak ekstremisme dan sekularisasi modernitas, tetapi memiliki titik tekan yang berbeda dalam gagasan pembaruan Islam. Ahmad al-Tayyeb menekankan turath, moderasi Islam, kesinambungan tradisi keilmuan, dan dialog antaragama, sedangkan Haedar Nashir menonjolkan Islam Berkemajuan, transformasi sosial, pendidikan, serta pluralisme kewargaan. Penelitian ini menegaskan bahwa pembaruan Islam berkembang secara kontekstual, etis, dan kelembagaan sesuai dengan lingkungan sosial masing-masing. Temuan ini menawarkan kontribusi baru berupa kerangka komparatif antara paradigma pembaruan Islam berbasis otoritas keagamaan Timur Tengah dan gerakan Islam modern Indonesia, sehingga memperluas pemahaman tentang pluralitas model tajdid Islam kontemporer.